2014
DOI: 10.1080/09537325.2014.951319
|View full text |Cite
|
Sign up to set email alerts
|

Archetypes of governance for science and technology labs

Abstract: While policy-makers understand the vast benefits of publicly funded and not-for-profit research, governance practitioners have the difficult task of defining processes that can best foster high performance for science and technology (S&T) labs not primarily driven by profits. This qualitative study develops a new taxonomy based on two dimensions, the nature of the funding relationship between the parent organisation and the S&T lab and the degree of interdependence between the lab's research units. We discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Research on strategy process embraces a distinction between induced (or deliberate) and autonomous strategic behavior in organizations (Burgelman, 1983; Mintzberg, 1978), recognizing autonomous strategic behaviors as the foundational components of emergent (or bottom-up) strategy (Mirabeau & Maguire, 2014). Whereas induced strategic behaviors represent activities that are aligned with an organization’s prevailing strategic intent, autonomous strategic behaviors refer to activities that diverge from an organization’s extant strategic plans (or that may substitute for top-down strategic planning when it is lacking), and thus result in internal variation (Burgelman, 1991) characterized by misalignment or dissonance with the organization’s intended strategy (when one is present; Mirabeau, Kinder, & Malherbe, 2015; Mirabeau & Maguire, 2014). The prevalence of autonomous strategic behavior is reflective of line and middle managers’ roles as human agents of the organization.…”
Section: Line Managers’ Downward Involvement In Hrmmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on strategy process embraces a distinction between induced (or deliberate) and autonomous strategic behavior in organizations (Burgelman, 1983; Mintzberg, 1978), recognizing autonomous strategic behaviors as the foundational components of emergent (or bottom-up) strategy (Mirabeau & Maguire, 2014). Whereas induced strategic behaviors represent activities that are aligned with an organization’s prevailing strategic intent, autonomous strategic behaviors refer to activities that diverge from an organization’s extant strategic plans (or that may substitute for top-down strategic planning when it is lacking), and thus result in internal variation (Burgelman, 1991) characterized by misalignment or dissonance with the organization’s intended strategy (when one is present; Mirabeau, Kinder, & Malherbe, 2015; Mirabeau & Maguire, 2014). The prevalence of autonomous strategic behavior is reflective of line and middle managers’ roles as human agents of the organization.…”
Section: Line Managers’ Downward Involvement In Hrmmentioning
confidence: 99%
“…An organization’s strategic and structural contexts shape the environment within which middle and line managers make decisions and thus influence the nature and extent of their autonomous strategic activities. For instance, Andersen (2004) suggested that the distributed decision authority within a firm—defined as the extent to which middle managers can pursue new initiatives without obtaining permission from the organization’s top management team—may be influenced in part by the firm’s approach to budget allocations (Bower, 1982), a perspective reinforced by Mirabeau, Kinder, and Malherbe’s (2015) findings that science and technology labs that are supported by discretionary—as opposed to directed—funds take a less centralized and more autonomous approach to managing research portfolios. Interestingly, in a multiindustry sample of Dutch firms, Linder and Torp (2017) found no support for the effect of budgeting approaches on middle managers’ autonomous strategic actions, but found evidence that stronger boundary systems, characterized by formal communication and strong guidelines around appropriate behavior, and middle manager autonomy positively predicted autonomous strategic actions by middle managers.…”
Section: Line Managers’ Downward Involvement In Hrmmentioning
confidence: 99%
“…These types of specific radical innovations are aimed at research laboratories 14 and adopted by high-skilled users, such as researchers in basic and applied sciences (cf. Almirall and Wareham, 2011;Ritala and Sainio, 2014;Mirabeau et al, 2014). Lab-oriented radical innovation is a vital means to increase the performance and capabilities of the users in the discovery process 15 , and in general in the scientific research.…”
Section: Hencementioning
confidence: 99%
“…The main properties of these specific lab-oriented radical innovations (LABORINs), which support discovery process and scientific discoveries, are: within the research lab and spur multiplicity of stimuli during the discovery process to achieve scientific goals and/or to solve problems; this role in the learning process reinforces the ability to identify and control key elements of the discovery process so that knowledge can be successfully accumulated to produce effective 'know-how' " (cf. v. Tunzelmann et al 2008, p. 479;Almirall and Wareham, 2011;Mirabeau et al, 2014));…”
mentioning
confidence: 99%